Strategi Pemasaran Syariah Pada Produk Tabungan Tarbiyah di BMT UGT Sidogiri Capem Banyuwangi - Bibit Wahyudi; Aula Izatul Aini (JPSDa: Jurnal Perbankan Syariah Darussalam, 2021)
The research method used is descriptive qualitative, with a case study approach. The data analysis tool used is the IFAS, EFAS and SWOT analysis. The results show the distribution strategies used by BMT in exploiting the strengths of the opportunities that have been identified: BMT optimizes employee performance to keep up with the ever-increasing population, maintains the good name of the cooperative to attract sympathy for prospective members, strengthens the good name of BMT in the community by implementing the sharia system and performs a direct approach with the middle to lower society in particular. In minimizing weaknesses in order to take advantage of opportunities: increase the frequency of training for human resource supplies, improve technology-based facilities and continue to actively publish products on various media. In using strength to overcome threats: BMT develops and adapts marketing models, creates more attractive product variation styles and maintains the characteristics of sharia-based products. In minimizing weaknesses in order to avoid threats: conducting training programs to increase employee competence, spreading the name of sharia when involved in the field and optimizing marketing in all media.